Workload estimation of harvesters during the operations of work cycle - Golyakevich, Sergey; Goronovsky, Andrei (Transport, 2013)
The research is devoted to the investigation of working efficiency and workload of harvesters. The complex criterion of their efficiency evaluation is suggested. The estimation of operational effectiveness of the harvester MLH-414 (MЛX-414) in various working conditions has been made. The various styles of limbing have been analysed. The recommendations for the efficient application of a work mix have been given. Mathematical modelling of harvester loading during transport and engineering operations has been carried out. The adequacy of the designed model of the actual harvester structure has been verified. The most overloaded operations of the harvester's working cycle are defined. The ways for decreasing the emerging loadings are offered.First Published Online: 11 Oct 2013